Crystal structure of 1,3-di-tert-butyl-2-chloro-1,3,2-diazaphosphorinane − a saturated six-membered phosphorus nitrogen heterocycle with a partially flattened chair conformation and a long PIII—Cl bond - Erik Mecke; Walter Frank (Acta Crystallographica Section E: Crystallographic Communications, 2019)
Colourless blocks of 1,3-di-tert-butyl-2-chloro-1,3,2-diazaphosphorinane, C11H24ClN2P (1), were obtained by sublimation in vacuo slightly above room temperature. The asymmetric unit of the monoclinic crystal structure of the six-membered N-heterocyclic compound is defined by one molecule in a general position. The six-membered ring of the molecule adopts a cyclohexane-like chair conformation; the chair at one side is to some extent flattened as a result of the approximately trigonal–planar coordination of both nitrogen atoms. In detail, this modified chair conformation is characterized by an angle of 53.07 (15)° between the plane defined by the three carbon atoms and the best plane of the two nitrogen atoms and the two carbon atoms bound to them, and an angle of 27.96 (7)° between the latter plane and the plane defined by the nitrogen and phosphorus atoms. The tert-butyl groups are oriented equatorially and the chloro substituent is oriented axially. The P—Cl bond length of 2.2869 (6) Å is substantially longer than the P—Cl single-bond length in PCl3 [2.034 Å; Galy & Enjalbert (1982). J. Solid State Chem. 44, 1–23]. Inspection of the intermolecular distances gives no evidence for interactions stronger than van der Waals forces. The closest contact is between the Cl atom and a methylene group of a neighbouring molecule with a Cl...C distance of 3.7134 (18) Å, excluding a significant influence on the P—Cl bonding.